The blues of Jan de Bray's Judith and Holofernes: A technical study of two blue pigments and its impact on treatment. Issue 4 (2nd October 2019) - Albertson, Gerrit; Krekeler, Anna; van Loon, Annelies; Gaibor, Art Proaño; Noble, Petria
ABSTRACT: Round and ring-shaped abrasions and whitish islands were observed with a digital microscope in a degraded area of blue paint in Jan de Bray's (1626/7–1697) Judith and Holofernes, 1659, a Dutch panel painting from the collection of the Rijksmuseum in Amsterdam. Although whitish islands have been previously reported as degradation deposits in ultramarine paint layers, it was unclear in this painting if the islands were remains of abraded paint, degradation deposits, or both. Non-invasive and micro-sampling techniques were used to study the materials and damage phenomena. Two blue pigments were identified in the blue blanket: indigo and ultramarine. The whitish islands were characterized as remnants of an abraded and degraded ultramarine paint layer used for the midtones and highlights on top of an indigo-containing blue-gray underlayer. The authors propose a possible mechanism for discoloration and damage to the ultramarine paint layer. Deposits of palmierite, a lead-potassium-sulfate compound, were also detected in the blue paint layers of the blanket but are not considered a significant component of the whitish islands. The likely presence of alum in the indigo may explain a UV-induced visible fluorescence observed in the indigo-containing paint layers. Ultimately, the results of the study were used to inform the retouching stage of treatment.